Desain Industri Perdagangan Minyak Sawit di Kota Dumai - Amiroel Oemara Syarief (Jurnal Hukum Respublica, 2018)
The purpose of this study: First, to explain the industry and trade in palm oil in Dumai City? Second, to explain the review of the cancellation of the study design of the palm oil industry in Dumai City. This type of research is normative (normative juridical). The results of this study can be explained in the city of Dumai there are two large groups of companies that compete in the palm oil trading industry, namely Wilmar Group and Asian Agri Group. When viewed from the industrial design in Dumai City, the researchers did not find any dispute about the good industrial design between designs issued by Wilmar Group and Sari Dumai Sejati which both produce palm oil.